Innovations to overcome the increasingly complex problems of hunger - Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2018)
Hunger has become ever more complex, and therefore efforts to sustainably eradicate hunger and malnutrition depend on policies and programs that match these complexities. Innovations are critical for progress. However, they require increased public and private investments as well. Key elements of inclusive policies and partnerships are agricultural development in the hunger-affected rural areas and communities to improve productivity will remain a major part of solutions. Farmers' own innovation capacities need strengthening. Investment in food and agricultural research and development (R&D) is an important tool for broad-based innovation, for instance, related to improved seeds. Digital technology is a game changer for food and nutrition security. Innovations for improved market functioning and avoidance of price shocks require information and early warning systems, as well as better preparedness with improved trade and food reserves policies. The environmental and climate change aspects of agricultural and land and water use change need more attention for sustainable hunger reduction. More attention to innovative social protection and direct nutrition intervention programs is needed, including addressing the micronutrient deficiencies in rural and urban areas. Hunger in complex emergencies needs to bring together development policy with diplomacy and security policy. Innovation initiatives like any development investments must follow principles of good governance, achieving investment at low transaction costs, sound financial practices, and avoidance of diversions of funds.
Keywords: O3; O13; Q16; Q18; 330; food security; nutrition; agricultural development; innovation; digital technology; social innovation